Early Growth Enhancement of Calliandra calothyrsus Meissn By Arbuscular Mycorrhizae Fungi and Coconut Shells Charcoal at Marginal Soil FUNGI MIKORIZA ARBUSKULA DAN ARANG TEMPURUNG KELAPA MEMPERCEPAT PERTUMBUHAN AWAL BIBIT Calliandra calothyrsus MEISSN - Sri Wilarso Budi R.; Sabti Indah Purwanti; Maman Turjaman (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2015)
One of the characteristic of marginal soil is low nutrient avaibility due to their low pH and low organic content. Such conditions become limiting factor for plant growth and development. In order to support optimal growth of plant, soil treatment is needed AMF and coconut shells charcoal have a potential to improve plant growth in marginal soil. This study aimed to examine the effect of AMF, coconut shells charcoal and their interaction on C. calothyrsus seedling grown in marginal soil. This study conducted split plot design in completely randomized design that consists of two factors. AMF factor as main plot consists of three levels, charcoal factor as sub plot consists of three levels. There were five replications for each treatment. The results showed that AMF and coconut shells charcoal significantly increased C. calothyrsus seedling growth. The best treatment was found at Gigaspora sp. combined with 20 % coconut shells charcoal increased height and diameter by 397.1 and 107.7% respectively (compared to control).Key words: AMF, Charcoal, Calliandra calothyrsus, growth